Socioeconomic differences in swimming ability among children in Malmö, southern Sweden: Initial results from a community-level intervention. Issue 5 (July 2020) - Pilgaard, Frida I. H.; Östergren, Per-Olof; Olin, Anna; Kling, Stefan; Albin, Maria; Björk, Jonas
Aims: To investigate to what extent socioeconomic differences in swimming abilities persist among children in the city of Malmö, Sweden, after a community-level swimming intervention programme in public primary schools. Methods: A compulsory swimming education programme was launched in 2014 in second grade (at age 8) in all public primary schools in Malmö, Sweden. Data for the present study on sociodemographic conditions and self-reported swimming ability in fourth grade (age 10) were used for the last birth cohort unexposed ( n = 1695) and the first birth cohort exposed ( n = 1773) to the intervention. Results: The swimming ability was 78 and 77%, respectively, in the pre- and post-intervention cohorts. Significantly lower self-reported swimming ability was found both pre- and post-intervention among children with support activities in school, with parents born outside Europe, North America and Australia, with manual working, unemployed or studying parents and in children enrolled in schools with socioeconomic index below median. Conclusions : The findings do not suggest that sociodemographic differences in swimming ability have decreased in the first birth cohort exposed to the community-level intervention in Malmö. Striking differences in self-reported swimming ability were noted when the children reached the fourth grade both pre- and post-intervention with marked lower abilities in socially disadvantaged groups. Monitoring of swimming abilities should continue for the present, and similar interventions aimed at reducing inequalities among children. Efforts to increase water comfort at preschool age ought to be considered.